а) 5а + (-b) = 5a - b
б) а³ + (-2а) + (-b²) = a³ - 2a - b² = a³ - b² - 2a
в) а² + (-b²) = a² - b²
г) a + (-3b) + 1 = a - 3b + 1 = -3b + a + 1
В решении.
Объяснение:
1.
а) 9a² – 12ab + 4b² = квадрат разности =
= (3a - 2b)²;
б) (3a – 2b)² = квадрат разности=
= 9a² - 12ab + 4b²;
в) 9a² – 4b² = разность квадратов=
= (3a - 2b)*(3a + 2b);
г) (3a + 2b)² = квадрат суммы =
= 9a² + 12ab + 4b²;
Разложите на множители:
16k² – 49п² = разность квадратов=
= (4k - 7n)*(4k + 7n);
2.
а) (4k – 7n)² = квадрат разности=
= 16k² - 56kn + 49n²;
б) (16k – 49n)² = квадрат разности=
= 256k² - 1568kn + 2401n²;
в) (4k – 7n)(4k + 7n) = разность квадратов=
=16k² - 49n²;
г) (4k + 7n)² = квадрат суммы=
= 16k² + 56kn + 49n².
Объяснение:
а)5a-b
б)a³-2a-b²
в)a²-b²
г)a-3b+1